Diet and Lifestyle Changes During the COVID-19 Pandemic in Ibero-American Countries: Argentina, Brazil, Mexico, Peru, and Spain - Enriquez-Martinez, Oscar G.; Martins, Marcia C. T.; Pereira, Taisa S. S.; Pacheco, Sandaly O. S.; Pacheco, Fabio J.; Lopez, Karen V.; Huancahuire-Vega, Salomon; Silva, Daniela A.; Mora-Urda, Ana I.; Rodriguez-Vásquez, Mery; Montero López, M. Pilar; Molina, Maria C. B. (Frontiers in Nutrition, 2021)
This study aimed to evaluate changes in dietary and lifestyle habits during the period of confinement due to the first wave of the COVID-19 pandemic in Ibero-American countries. A cross-sectional investigation was conducted with 6,325 participants of both genders (68% women), over 18 years of age and from five countries: Brazil (N = 2,171), Argentina (N = 1,111), Peru (N = 1,174), Mexico (N = 686), and Spain (N = 1,183). Data were collected during the year 2020, between April 01 and June 30 in Spain and between July 13 and September 26, in the other countries studied using a self-administered online survey designed for the assessment of sociodemographic, employment, physical activity, health status, and dietary habits changes. Most participants (61.6%), mainly those from Spain, remained constant, without improving or worsening their pattern of food consumption. Among those who changed, a pattern of better eating choices prevailed (22.7%) in comparison with those who changed toward less healthy choices (15.7%). Argentina and Brazil showed the highest proportion of changes toward a healthier pattern of food consumption. Peruvians and Mexicans were less likely to make healthy changes in food consumption (OR: 0.51; 95% CI: 0.4–0.6 and OR: 0.69; 95% CI: 0.4–0.8, respectively), when compared to Argentinians. Most respondents did not change their pattern of meal consumption, but those who did reduced their consumption of main meals and increased intake of small meals and snacks. Although most participants affirmed to be doing physical activity at home, about one-half reported perception of weight gain. Individuals with alterations in sleep pattern (either by increasing or decreasing sleep time) were more likely to change their diets to a healthier pattern. In contrast, individuals with confirmed diagnosis of COVID-19 and those who reported feeling anxious were more likely to perform changes to a less healthy eating pattern (OR: 1.72; 95% CI: 1.2–2.3 and OR: 1.21; 95% CI: 1.1–1.4, respectively). In conclusion, although most participants remained constant in their eating habits, lifestyle changes and anxiety feelings were reported. Among those who changed patterns of food consumption, healthier choices prevailed, with differences between countries. However, there were alterations in the distribution of meals, with higher consumption of snacks and small meals. These results can be used to guide policies to prevent deleterious consequences that may affect the incidence of chronic diseases.